Direct observation of stepwise movement of a synthetic molecular transporter. - Wickham, S; Endo, M; Katsuda, Y; Hidaka, K; Bath, J; Sugiyama, H; Turberfield, A (Nature Publishing Group, 2011)
Controlled motion at the nanoscale can be achieved by using Watson-Crick base-pairing to direct the assembly and operation of a molecular transport system consisting of a track, a motor and fuel, all made from DNA. Here, we assemble a 100-nm-long DNA track on a two-dimensional scaffold, and show that a DNA motor loaded at one end of the track moves autonomously and at a constant average speed along the full length of the track, a journey comprising 16 consecutive steps for the motor. Real-time atomic force microscopy allows direct observation of individual steps of a single motor, revealing mechanistic details of its operation. This precisely controlled, long-range transport could lead to the development of systems that could be programmed and routed by instructions encoded in the nucleotide sequences of the track and motor. Such systems might be used to create molecular assembly lines modelled on the ribosome.